Professional Development of Italian Primary School Teachers who Teach English. What Prospects after B1 Certification? - Cristina Richieri (Pensa MultiMedia, 2019)
The article deals with the issue of the training of Italian teachers who teach English in primary school. The development of the teaching of foreign languages, including English, in Italy is briefly illustrated from the historical and regulatory points of view together with the state-of-the-art in the field of teacher professional development in Europe. Then, the Keep Up Your English (KUYE) course, which is still in progress, is presented. The course has been activated to satisfy the demand for further linguistic and methodological training expressed by some Italian primary school teachers already in possession of B1 level certification (CEFR) and, therefore, having title to teach English in their classes according to the current legislation. Then, a research carried out within the KUYE course to understand the teachers' motivations and learning needs is presented. The discussion of the data also focuses on concerns, perceptions, awareness and learning strategies which can be activated by using ICT. The research, which will be completed once the course is over, highlights a critical issue, already known, in the institutional training of this category of teachers, i.e. that of lack of its continuity and, at the same time, offers some suggestions for overcoming this.